The Effect of Studying in Selective Classes on the Change in Pupils’ Action-Control Beliefs During Lower Secondary School in Finland - Satu Koivuhovi; Mari-Pauliina Vainikainen; Mira Kalalahti (Scandinavian Journal of Educational Research, 2022)
Tracking pupils based on their abilities or other aptitudes is a common practice in many countries. In Finland, selective classes with a special emphasis have become popular. The societal and individual effects of tracking are a topic of ongoing educational discussion. Tracking has been seen to increase educational inequality, but still it has been defended as an important practice enabling individualised and adjusted teaching. This study examined whether studying in a selective class with a special emphasis has an effect on the development of pupils' action-control beliefs from grade seven to nine. Results showed that pupils who studied in classes with a special emphasis showed greater achievement and were more likely to have highly-educated mothers than pupils in classes without an emphasis. This selectivity explained most of the differences found in action-control beliefs between classes. Pairwise comparisons showed small differences in the change of certain action-control beliefs between classes.